From Chaos to Order: Synergetic Society, Synergic Administration and Synergistic Planning Case Study: The Building Process of a Primary School in the Process of Self-Organization after the 1999 Marmara Earthquakes - Diker, Nazire; Okten, Ayse Nur (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2009)
In contemporary societies, through the advances in the technologies of informatics and communication, global interactions are increased, and developments, variations, changes, and transformations in any field are shared more rapidly than at any previous time in human history. Existing systems have been unable to show the necessary flexibility regarding the new requirements and the problems of new relations due to unpredictable circumstances. This can lead to the perception of chaotic societies and cause ontological problems in planning, which is based on future predictions. The main goal of this paper is to summarize the synergetic society model, synergic administration and synergistic planning approaches (developed for the dissertation). These concepts will help us to understand uncertain and unpredictable social changes. According to our model, social synergy, which is spontaneously emerging and organizing via communication channels, is thoroughly examined in the processes of chaos and self-organization as experienced following the eastern Marmara earthquake in 1999. The building process of a primary school with the help of social synergy in Kilicky /Yalova after the earthquake is explained on the basis of communication channels between different levels and with varying dynamics.
Keywords: Chaos; earthquake; self-organization; social synergy; synergetic; synergetic society model; synergic administration; synergistic planning; Architecture